SEM image-guided manipulation with a feedback assistance system for automated nanohandling of a 4 DOF micromanipulator. (13th October 2021) - Dey, Ujjal; Kumar, C S; Jacob, Chacko
Abstract: Nanohandling of a robotic system inside an scanning electron microscope (SEM) to manipulate and characterize nanomaterials is a complex task for any user with manual control strategies. Therefore, the need for automation of these robotic systems is increasing rapidly for various interdisciplinary applications in nanotechnology. Here an automatic handling procedure of a piezo-driven nanomanipulation system is described using the SEM vision system as a feedback device for position-based visual servoing closed-loop control. A web-based integrated control interface is designed for the manipulator's control, which allows a user to command the manipulator for positioning at any desired location within the working space's view field. It helps in the quick automatic nanopositioning task of the robot end-effector for any required application. The control technique is further applied to demonstrate a manipulation task with spherical shape polystyrene nanoparticles. Additionally, we propose a 3D offline simulation visualization of the manipulation system in the SEM view, which gives virtual configurational feedback of the manipulators and also helps in manipulation task planning.